Developing an Emergency Offshore Hazard Map and risk assessment indices using Spatial Decision Support System (SDSS) - Wong, Kelvin Toh Kiak (Universiti Teknologi PETRONAS, 2017)
Offshore emergencies such as oil spill present a serious threat to the coastal environment. Consequently, response teams need to act fast in order to minimize the damage done to the environment in the vent of accidental oil spills. This study proposes to use spatial decision support system (SDSS) in assisting decision makers and response teams in their plan to effectively handle offshore emergency and mitigate potential effects. A structured GIS-based multi criteria decision making (MCDM) model is implemented by combining the analytical hierarchy process (AHP) with GIS to develop an emergency offshore hazard map and risk indices. The coastal area of East Malaysia was used as the study area to test the SDSS. A sensitivity index of five categories (very high, high, medium, low, and very low) were produced for the coastline of East Malaysia. The produced map will be useful in offshore emergency such as oil spill to help response team develop and implementing a successful response plan.